Restorative Justice Through Strengthening Community Legal Culture in Indonesia: Challenges and Opportunity - Mulyana Hadi, Adwi; Iftitah, Anik; Alamsyah, Syahrul (Faculty of Law, Mulawarman University, 2023)
The main objective of this study is to examine how restorative justice can be effectively implemented in Indonesian society by strengthening its legal culture. The research methodology employed in this investigation is normative research, which encompasses a comprehensive review of existing literature and an analysis of pertinent legislation and policies. The prevailing legal culture in Indonesia places significant emphasis on punishment and incarceration as forms of justice, thereby influencing the acceptance and execution of restorative justice practices. Nevertheless, various endeavors have been undertaken to integrate restorative justice into the community's legal culture. These initiatives include establishing supportive legal frameworks, providing training and capacity-building programs, implementing pilot projects and experiments, advocacy campaigns, public awareness campaigns, and community engagement. However, several obstacles and challenges need to be addressed, such as shifting legal paradigms, insufficient knowledge and awareness among the general public, resistance from offenders, and limited resources. To overcome these constraints and challenges, concrete steps are needed, such as increasing public knowledge and awareness, establishing supportive legal frameworks, active community engagement, and resource optimization. By addressing these constraints and challenges, restorative justice can be more integrated with the legal culture of Indonesian society, providing a positive contribution to conflict resolution, restoring social relationships, and improving the justice system in Indonesia.